Blood Genome-Wide Transcriptional Profiles of HER2 Negative Breast Cancers Patients - Ovidiu Balacescu; Loredana Balacescu; Oana Virtic; Simona Visan; Claudia Gherman; Flaviu Drigla; Laura Pop; Gabriela Bolba-Morar; Carmen Lisencu; Bogdan Fetica; Oana Tudoran; Ioana Berindan-Neagoe (Mediators of Inflammation)
Tumors act systemically to sustain cancer progression, affecting the physiological processes in the host and triggering responses in the blood circulating cells. In this study, we explored blood transcriptional patterns of patients with two subtypes of HER2 negative breast cancers, with different prognosis and therapeutic outcome. Peripheral blood samples from seven healthy female donors and 29 women with breast cancer including 14 triple-negative breast cancers and 15 hormone-dependent breast cancers were evaluated by microarray. We also evaluated the stroma in primary tumors. Transcriptional analysis revealed distinct molecular signatures in the blood of HER2− breast cancer patients according to ER/PR status. Our data showed the implication of immune signaling in both breast cancer subtypes with an enrichment of these processes in the blood of TNBC patients. We observed a significant alteration of “chemokine signaling,” “IL-8 signaling,” and “communication between innate and adaptive immune cells” pathways in the blood of TNBC patients correlated with an increased inflammation and necrosis in their primary tumors. Overall, our data indicate that the presence of triple-negative breast cancer is associated with an enrichment of altered systemic immune-related pathways, suggesting that immunotherapy could possibly be synergistic to the chemotherapy, to improve the clinical outcome of these patients.